COMMUNICATION PATTERNS OF THE SCHOOL AND GUARDIANS OF STUDENTS IN THE ESTABLISHMENT OF PROTECTED AND virtuous CHARACTERS OF STUDENTS IN SD NEGERI 3 NGARINGAN, NGARINGAN DISTRICT, GROBOGAN REGENCY - Maftukatul Ijtihabah, Nanang Nur Cholis (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
ABSTRACTThe purpose of this study was to find out and describe 1) the communication patterns of the school and the guardians of students in shaping the polite and virtuous character of the students at SD Negeri 3 Ngaringan, 2) the supporting and inhibiting factors of the communication pattern of the school and the guardians of students in forming a polite and respectful character. virtuous students at SD Negeri 3Ngaringan, 3) the implications of communication between the school and student guardians on the polite and virtuous character of students at SD Negeri 3 Ngaringan. The approach used in this study is a qualitative approach using a descriptive perspective. Data collection techniques consist of in-depth interviews, observation and documentation. Data analysis in this study was carried out using an interactive analytical model developed by Miles and Huberman including data collection, data reduction, data presentation and drawing conclusions. The results of the research are the first. The pattern of communication between the school and student guardians in shaping the polite and virtuous character of students at SD Negeri 3 Ngaringan, namely 1) formal communication consisting of: contact books, student report cards, official invitation letters. 2) non-formal communication consisting of: home visits, through whatshap groups and telephones, PHBI Religious activities. Second. The inhibiting factors for the communication pattern of the school and the guardians of students in shaping the polite and virtuous character of students at SD Negeri 3 Ngaringan are 1) internal factors, namely: the teacher's view of parents, fear of building communication with parents, facilities and infrastructure are stillinadequate 2) External factors are the busyness of parents with their work, there are parents who are less supportive of the implementation of character education programs such as not signing student activity books. Third. The implications of communication between the school and the guardians of students on the polite and virtuous character of students in SD Negeri 3Ngaringan namely students are more diligent in studying and never play truant, there are no students who fight, students orderly worship in congregation and uphold the values of akhlakul karimah, religious aspects, students always pray five times a day. a penchant for reading, students take advantage of their free time, the level of self-confidence and self-reliance of students is very good.Keywords: Communication Pattern of School and Student Guardians, Formation of polite and virtuous character